Development and optical characteristics of the macroporous silicon structures - Karachevtseva, L.A.; Lytvynenko, O.A.; Stronska, O.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The promising material for the 2D photonic structure formation for infrared spectrum range is macroporous silicon. There was investigated the electrochemical process of the cylindrical pore formation on n-Si plates for linear change of applied voltage. The experimental dependences of the regimes of macropore formation correspond to the diffusion-drift model of the nonequilibrium hole transfer for the anode thickness, that exceed the length of hole diffusion and for comparatively big macropore radii. Optical transmission of the macropore structures was measured and was equal to 10⁻² comparing to that of homogeneous material; surface recombination component was estimated.